2019
DOI: 10.1097/pts.0000000000000585
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender, Profession, and Managerial Function on Clinicians’ Perceptions of Patient Safety Culture: A Cross-National Cross-Sectional Study

Abstract: Objectives In recent years, several instruments for measuring patient safety culture (PSC) have been developed and implemented. Correct interpretation of survey findings is crucial for understanding PSC locally, for comparisons across settings or time, as well as for planning effective interventions. We aimed to evaluate the influence of gender, profession, and managerial function on perceptions of PSC and on the interplay between various dimensions and perceptions of PSC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 24 publications
8
23
1
4
Order By: Relevance
“…Interestingly, nurses benefited most from the trial intervention in terms of perceived patient safety (3.19 ± .62 vs. 3.78 ± .54, p = .002) resulting in slightly higher scores than physicians in the post-interventional phase. Similar results were found elsewhere [ 20 , 21 ]. Why nurses are more sensitive to perceive deficits in patient safety has not yet been further evaluated.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, nurses benefited most from the trial intervention in terms of perceived patient safety (3.19 ± .62 vs. 3.78 ± .54, p = .002) resulting in slightly higher scores than physicians in the post-interventional phase. Similar results were found elsewhere [ 20 , 21 ]. Why nurses are more sensitive to perceive deficits in patient safety has not yet been further evaluated.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning results for individual SAQ factors in our explorative analysis, physicians scored higher than nurses in most items, especially in items concerning teamwork climate (3.84 ± 0.52 vs. 3,58 ± 0.62, p = 0.032) and stress recognition (3.97 ± 0.75 vs. 3.17 ± 0.92, p < 0.001), where higher scores indicate a better sensitivity for the impact of stress (Figure 1). Similar results were found elsewhere (25,26). These might indicate different perceptions of teamwork and stress identify nurses as a particularly vulnerable group.…”
Section: Discussionsupporting
confidence: 87%
“…The large variability in terms of the reliability and validity of the HSPSC across our sample might be due to the influence of professional groups and other subcultures within healthcare 30 62. Many HSPSC items may be very differently interpreted and may elicit very different opinions among different healthcare groups (eg, nursing staff, physicians and managers31 63).…”
Section: Discussionmentioning
confidence: 98%
“…One explanation for low levels of reliability and validity may be the different interpretations of what constitutes a positive PSC among the diverse occupational groupings and subcultures involved in healthcare delivery 28–30. Previous work, for example, has shown that physicians report higher levels of PSC when there is good teamwork across units and a unit-level management that promotes PSC 31. Nursing staff, by contrast, are more likely to report higher levels of PSC safety when they feel that there is enough staff in the unit 31–33.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation